Mejoramiento varietal - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1981)
During 1981 genotype evaluation and selection continued at the ICA (Instituto Colombiano Agropecuario)-Caribia and the ICA-CIAT- Carimagua stations and at CIAT-Palmira, considered representative sites, resp., of (1) low-input technology with medium to high fertility soils in hot, lowland tropics (edaphoclimatic zone I), (2) low- to medium-input technology with extremely low fertility soils in the tropical savannas (edaphoclimatic zone II); and (3) low-input technology with high fertility soils in the medium alt. tropics (edaphoclimatic zone IV). In zone IV, there has been a steady upward trend in root yield as of 1973, with current av. yields of 40 t/ha and max. yields of 60 t/ha with more than 35 percent DM. In zone I, av. yields of 40 t/ha with more than 30 percent DM are also obtained. In zone II, F1 clones have already outyielded local cv., mainly due to improved resistance to CBB and superelongation disease (Sphaceloma manihoticola). Advances in yield stability were analyzed on the basis of spatial stability (macro and microspatial), system stability (over fertility levels and over farm management), and temporal stability (especiallyregarding the nature of resistance to CBB and the superelongation disease, quality of planting stakes, deterioration of cv., and unforeseen factors). Aspects related to economically valid yields are analyzed: root DM content and eating quality, root perishability, HCN content, and ease of harvest. CIAT's capacity for production and distribution of hybrid seeds has increased; 30,000 seeds are used each year in the selection process and approx. another 20,000 seeds are sent to collaborating national programs. (CIAT)